Pendugaan Emisi CO2 dan Kebutuhan O2 Serta Daya Serap CO2 dan Penghasil O2 Pada Taman Kota dan Jalur Hijau di Kota Medan - Ahmad Rivai; Pindi Patana; Siti Latifah (Program studi Kehutanan USU, 2016)
Carbondioxide (CO2) produced by the fumes and industrial activities can harm humans if there are no trees or urban forests that can absorb CO2 and emissions resulting from human activities. Therefore, an effort to reduce air pollutants such as CO2 gas in urban areas, especially the city of Medan is a way to build a green open space in the form of urban forests. This study aimed to calculate the amount of CO2 emitted and the amount of O2 required in Medan based emissions from motor vehicles, human respiratory and industry and widely suspected optimal urban forest based on the function of absorbing CO2 and producing O2. Estimation results indicate that the total CO2 emissions in the city of Medan in 2014 amounted to 2,659,091.01 tons while demand for O2 in Medan in 2014 amounted to 2,430,843.07 tons . So the ability of the urban forest in the form of urban parks and green line in absorbing CO2 14683.84 tons and the capability of producing O2 amounted to 5551.2 tons .Keywords : CO2 emissions , O2 Demand, CO2 Absorbance, O2 Production, city park, green belt.